2019
DOI: 10.1002/aur.2153
|View full text |Cite
|
Sign up to set email alerts
|

Typical perceptual organization in autism: Perceptual grouping and spatial distortion

Abstract: The extensive literature on global–local processing in people with autism spectrum disorder (ASD) has recently shifted from arguing for a processing impairment among those with ASD to positing an attenuated preference for global processing. One suggestion is that the fast extraction of the global gist is less efficient in ASD, in contrast to the superior attention‐driven processing of local elements. To examine this claim of attenuated global processing, the present study tested how perceptual grouping affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
1
8
1
Order By: Relevance
“…Concordantly, when tested implicitly using object-based attention effects, grouping by proximity among persons with ASD was, as we found, comparable to that of TD individuals (Falter et al, 2010). Similarly, persons with ASD showed similar effects of Gestalt grouping on perceptual estimations to those displayed by their TD peers on an implicit task of distance estimation examining the organization of visual scenes (Avraam et al, 2019). The convergent evidence from these studies indicates intact utilization of Gestalt cues in element clustering and perceptual organization of visual scenes, and their interactive effects in shape formation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Concordantly, when tested implicitly using object-based attention effects, grouping by proximity among persons with ASD was, as we found, comparable to that of TD individuals (Falter et al, 2010). Similarly, persons with ASD showed similar effects of Gestalt grouping on perceptual estimations to those displayed by their TD peers on an implicit task of distance estimation examining the organization of visual scenes (Avraam et al, 2019). The convergent evidence from these studies indicates intact utilization of Gestalt cues in element clustering and perceptual organization of visual scenes, and their interactive effects in shape formation.…”
Section: Discussionsupporting
confidence: 79%
“…The notion that the discrepant evidence is task-dependent is supported by the finding that participants with ASD were able to organize the whole representation utilizing the grouping cues of closure, good continuation, similarity, and proximity when the task involved element clustering (Avraam, Binur, & Hadad, 2019). Both the participants with ASD and the TD participants underestimated spatial distances within elements composing a perceived group, but overestimated those between elements composing two different perceived groups.…”
Section: Use Of Gestalt Shapes To Assess Wcc and Epfmentioning
confidence: 99%
“…The fast extraction of the global gist was less efficient in ASD than in TD; by contrast, attentiondriven processing of local elements was superior. Avraam et al reported attenuated global processing in ASD [51]. A higher frequency of ASD occurrence has been reported in previous studies [52].…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, Milne and Scope (2008) used a forced choice judgment of the dimensions of a shape defined by illusory contours-and contrary to Happé's study which used the same displays-found no differences between those with and without autism. Hadad and colleagues Binur, Hel-Or, & Hadad, 2021;Avraam, Binur, & Hadad, 2019) used 2AFC tasks and found typical susceptibility to the width-height illusion and the weightbrightness illusion, both involving integration across dimensions, with the latter also involving integration across sensory modalities. The findings, thus, converge across these psychophysical studies to suggest typical effects of perceptual illusions in autism.…”
Section: Coherent Picture Of Visual Illusionsmentioning
confidence: 99%